Combinatorial therapy with three-dimensionally cultured adipose-derived stromal cells and self-assembling peptides to enhance angiogenesis and preserve cardiac function in infarcted hearts - Kim, Ji Hyun; Park, Yongdoo; Jung, Youngmee; Kim, Soo Hyun; Kim, Sang-Heon (WILEY, 2017)
Even though stem cell therapy is a promising angiogenic strategy to treat ischaemic diseases, including myocardial infarction (MI), therapeutic efficacy is limited by low survival and retention of transplanted cells in ischaemic tissues. In addition, therapeutic angiogenesis depends on stimulating host angiogenesis with paracrine factors released by transplanted cells rather than on direct blood vessel formation by transplanted cells. In the present study, to overcome these limitations and to enhance the therapeutic efficacy of MI treatment, combinatorial therapy with three-dimensional cell masses (3DCMs) and self-assembling peptides (SAPs) was tested in a rat MI model. Spheroid-type 3DCMs, which are vascular differentiation-induced cells, were prepared by culturing human adipose-derived stromal cells on a fibroblast growth factor-immobilized surface. The SAPs were used as the carrier material to increase engraftment of transplanted cells. After coronary artery ligation, 3DCMs were combined with SAPs and were transplanted into ischaemic lesions. The therapeutic potential was evaluated 4 weeks after treatment. By combining 3DCMs and SAPs, survival and retention of transplanted cells increased threefold when compared with treatment with 3DCMs alone and transplanted cells established vascular networks in infarcted hearts. In addition, the size of the infarct in the 3DCM + SAP group was reduced to 6.09 +/- 2.83% by the promotion of host angiogenesis and cardiac function was preserved, as demonstrated by a 54.25 +/- 4.42% increase in the ejection fraction. This study indicates that combinatorial therapy with 3DCM and SAPs could be a promising strategy for therapeutic angiogenesis to treat MI. Copyright (C) 2016 John Wiley & Sons, Ltd.
Keywords: STEM-CELLS; MYOCARDIAL-INFARCTION; DELIVERY; REGENERATION; NANOFIBER; DIFFERENTIATION; BIOMATERIALS; ADHESION; EFFICACY; CLUSTER